2018
DOI: 10.1111/jth.13971
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor dampens tissue factor expression via nuclear factor‐κB and early growth response protein 1

Abstract: Background Prostate cancer is one of the leading causes of cancer death in men. Advanced prostate cancer is usually treated by androgen deprivation therapy (ADT), which is aimed at reducing circulating testosterone levels to reduce cancer growth. There is growing evidence that ADT can increase the rate of venous thromboembolism (VTE) in prostate cancer patients. The tissue factor (TF) gene is one of the most important mediators of coagulation and VTE, but, so far, there are limited data on androgen receptor (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Among these factors, tissue factor (TF) could interact with the coagulation factor FVII, triggering subsequent thrombin formation. ALK/ROS1 downstream NF-κB signaling might be involved in the expression of TF (52). Sen et al (53) found upregulation of TF in ALKfusion NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among these factors, tissue factor (TF) could interact with the coagulation factor FVII, triggering subsequent thrombin formation. ALK/ROS1 downstream NF-κB signaling might be involved in the expression of TF (52). Sen et al (53) found upregulation of TF in ALKfusion NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given that androgen receptor dampens tissue factor, a pivotal mediator of coagulation and VTEs, expression via nuclear factor-kappa B (NF-κB) and early growth response protein 1, increased tissue factor expression is expected in androgen-deprived prostate cancer patients ( 27 ). In another in vitro study, androgen receptor-positive prostate cancer cell lines did not trigger platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…We found 29 papers that used this antibody to measure human, mouse, rabbit and canine TF by a variety of methods, including 15 that used the antibody for western blotting (Table S1). 33‐61 Importantly, Abcam evaluated the ability of the antibody to detect human TF in wild‐type and KO cell lines by western blotting 62 . Based on the data they obtained, they recently withdrew ab151748 and stated that “after evaluation, using a HAP1 knockout cell line, ab151748 was not shown to react specifically with the target protein and has therefore been discontinued.” We confirmed that this antibody does not detect mouse TF by western blotting but rather a nonspecific band.…”
Section: Discussionmentioning
confidence: 99%